Entrepreneurship as a Route out of Poverty A Focus on Women and Minority Ethnic Groups - Olarewaju, Tolu (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
XVII, 150 p. 10 illus., 2 illus. in color.